Innovation of Writing Skills Assessment Instrument at the Creating Level in Arabic Language Textbooks - Ananda Zalfa Firdaus; R. Umi Baroroh (Kalamuna)
Writing skills assessment instrument in grade VIII MTs textbook shows that from the aspect of presentation it is systematic, coherent and consistent. But when viewed from aspect of the content writing skills assessment instrument it has not yet contained the level of creating. Even though writing skills are important controlled productive skills for students to master. Especially at level of creating to produce critical and creative writing ideas. The purpose of this study is to present an analysis and innovation of writing skills assessment instruments at creative level in Arabic language textbook for grade VIII MTs published by Ministry of Religious Affairs of the Republic of Indonesia in 2020 according to the criteria for learning writing skills. The method used in this study is literature study with a descriptive qualitative approach. The main source of this study is Arabic language textbook for grade VIII MTs and secondary source are books and articles on the assessment of Arabic writing skills and the level of creative. The result of this study shows instruments are needed in evaluating the learning of writing skills at level of creating. Innovation of this assessment instrument is expected to be a reference in evaluation of learning Arabic writing skills and encourage grade VIII MTs students to be more critical, creative and productive in writing.